Nonpharmacologic interventions for managing distress, anxiety, and depression for patients with cancer and their family caregivers: A systematic review and meta‐analysis - Lisa C. Schiess; Lixin L. Song; Sabine Schädelin; Thomas Fürst; Corinne Urech; Christopher R. Friese; Maria C. Katapodi (CA: A Cancer Journal for Clinicians, 2026)
Abstract As more cancer treatments take place in outpatient settings, family caregivers provide essential care and emotional support over long periods. Unaddressed patient and caregiver psychological distress can lead to worse outcomes, reflecting the challenges of managing complex care demands in the home setting. This systematic review and meta‐analysis examined how well nonpharmacologic interventions (NPIs) reduce distress, anxiety, and depression in adult patients with solid tumors and their family caregivers. The authors included 68 randomized controlled trials (RCTs) with a total of 11,987 participants. NPIs were characterized as psychoeducation, therapeutic counseling, skills training, or behavior modification. By using random‐effects models (Hedges g), they observed that NPIs significantly reduced patient distress at both 0.0–3.0 months (g = 0.13) and 3.1–6.0 months (g = 0.18), but NPIs did not significantly reduce caregiver distress. In the short term (0.0–3.0 months), NPIs also significantly reduced anxiety (g = 0.31 for patients; g = 0.15 for caregivers) and depression (g = 0.28 for patients; g = 0.25 for caregivers). Subgroup analyses examined the impact of patient and caregiver characteristics along with NPI type, delivery format, dose, and duration. NPIs delivered jointly to patients and caregivers yielded significant effects that were higher compared with NPIs delivered separately. NPIs can help manage distress in patients and reduce anxiety and depression in both patients and caregivers. However, the lack of long‐term follow‐up limits our understanding of their impact on patients and caregivers with prolonged or delayed psychological symptoms (PROSPERO registration number CRD42024536629).